2020
DOI: 10.1016/j.psj.2019.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding broiler breeder hens a coextruded full-fat flaxseed and pulses mixture without or with multienzyme supplement

Abstract: The effects of coextruded full-fat flaxseed and pulses ( FFF ; 1:1 wt/wt) mixture on n-3 polyunsaturated fatty acids ( PUFA ) enrichment in egg yolk, hepatic attributes, apparent retention ( AR ) of components, and ceca metabolites were evaluated in broiler breeder hens. The diets were as follows: 1) corn–soybean control, 2) control diet plus 18% FFF ( FFF− ), and 3) FFF plus enzyme supplement ( FFF+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In our current study, our flaxseed-fed hens had reduced body mass concomitant with reduced plasma AST [ 92 ]. Researchers from a separate lab observed 50% reduced hepatic crude fat content when hens were fed 18% coextruded full-fat flaxseed [ 93 ], corroborating our finding of reduced liver fat content.…”
Section: Discussionsupporting
confidence: 88%
“…In our current study, our flaxseed-fed hens had reduced body mass concomitant with reduced plasma AST [ 92 ]. Researchers from a separate lab observed 50% reduced hepatic crude fat content when hens were fed 18% coextruded full-fat flaxseed [ 93 ], corroborating our finding of reduced liver fat content.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the physicochemical characteristics of APL fiber and ensuing gastrointestinal effects could also have contributed. For example, broiler chickens (Thanabalan et al 2020) fed flaxseed exhibited reduced retention of NDF, which was associated with mucilage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported an increase in villi height in broilers and 51-wk-old laying hens fed diets containing whole flaxseeds ( Apperson and Cherian, 2017 ; Westbrook and Cherian, 2019 ). As flaxseeds contain high levels of soluble nonstarch polysaccharides, a more mature GIT has enhanced capacity to digest and absorb more of the available nutrients ( Leung et al, 2018 ; Thanabalan et al, 2020 ). As well, inclusion of the multicarbohydrase, although intended for the wheat ingredients in the diet, may have affected the digestibility of FFF and DMA – specifically in the later phases where dietary wheat inclusion was reduced, allowing the enzyme to act upon other ingredients.…”
Section: Discussionmentioning
confidence: 99%